Die Übertragung von mikrostrukturellen Eigenschaften aus der diskreten Versetzungsdynamik in Kontinuumsbeschreibungen - Stricker, Markus (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2017)
Physically motivated dislocation density based models for the description of plastic deformation do need information about the underlying processes in a homogenized form. A rate formulation for the formation of the glissile junction for usage in continuum descriptions is developed by using three-dimensional Discrete Dislocation Dynamics. Furthermore, a contribution to the understanding of grain boundary modeling in Discrete Dislocation Dynamics as well as continuum descriptions is made.